Implementation of Reciprocal Teaching Models to Increase The Capability of Writing Definition and Theorem in Simbolic Form - Ahmad Yani T; Cristina Lanteri (STKIP Singkawang, 2017)
This study aims to obtain objective information about increasing in writing skill about definitions and theorems in symbolic form students through RT models in the sets, all kind of relations and functions in set and logic courses. In addition, this study develop the ability of understanding of definitions and theorems, because the ability of students to write definitions and theorems in symbolic form will foster the ability of understanding of the definitions and theorems.The sample of this study are the first semester students in class A2 who follow sets and logic course in mathematics education program of PMIPA FKIP Untan 2016-2017. Implementation focus on subject, sets and all kind of relations and functions.The data collection conducted in providing achievement test after being given treatment. Form of test is Essai with 15 questions which consist of 4 questions from subject set, 8 questions from kind of relations and 3 questions from functions.The results showed if the Reciprocal Teaching Model is one of model that could improve the writing skill about definitions and theorems through symbolic form in the subject matter ; Sets, kind of relations, functions in Sets and Logic courses.